Cash flow vs funds flow statement / Rosni Julis - Julis, Rosni (1992)
The Statement of Source and Application of Fund is no longer valuable to the business entity. Due to that fact The Account Standard Committee had issued the ED 54 " Cash Flow Statement " on 26 July 1990. There are two methods recommended by the ED 54 which are the direct and indirect method.